2013
DOI: 10.1002/asi.22782
|View full text |Cite
|
Sign up to set email alerts
|

Situation normality and the shape of search: The effects of time delays and information presentation on search behavior

Abstract: Delays have become one of the most often cited complaints of Web users. Long delays often cause users to abandon their searches, but how do tolerable delays affect information search behavior? Intuitively, we would expect that tolerable delays should induce decreased information search. We conducted two experiments and found that as delay increased, a point occurs at which time within-page information search increases ; that is, search behavior remained the same until a tipping point occurs where delay increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 85 publications
2
14
0
Order By: Relevance
“…Their results provided support for the hypothesis related to page delay time, and the volume of information examined on each page -resulting in stickier webpages. A similar finding was also found by Taylor et al [33]. While these findings are interesting, it should be noted that subjects in the aforementioned studies did not issue their own queries.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…Their results provided support for the hypothesis related to page delay time, and the volume of information examined on each page -resulting in stickier webpages. A similar finding was also found by Taylor et al [33]. While these findings are interesting, it should be noted that subjects in the aforementioned studies did not issue their own queries.…”
Section: Introductionsupporting
confidence: 74%
“…Studies have shown that people perform better at a given task when an obstacle is in their way [23], and constraints may allow people to clarify and focus on the task at hand [19]. This can already be observed to a certain degree in the cost-interaction hypothesis [2], for examplewith increased querying costs leading to stickier results [33].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations